DOES WORK ENVIRONMENT EFFECT ON EMPLOYEE PERFORMANCE: CASE STUDY IN THE UNIVERSITY SECTOR OF LAHORE PAKISTAN. - Maria Shabir; Hamza Akram; Muhammad Usman Farooq; Muhammad Bilal; Rana Taseer Ali Raza (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The Present study explores the working environment and efficiency of employees in district Lahore Punjab, Province of Pakistan. It aims to test a model focused on five workplace dimension and their impact on employee efficiency. The data have been collected from 120 employees from University sector in Lahore and processed via the STATA software. Pearson correlational and regression analyses had used, to evaluate the relationship of the variables selected. The findings of the analysis indicate that the majority of employees are people under supervision. The correlation findings from Pearson demonstrate that all the independent variables are related strongly and significantly to employee achievement, particularly in the physical conditions of work that represent the most positive and essential relationship. In comparison, the findings of regression analyze indicate that employees' success depends primarily on physical working conditions and preparation as well as organizational activities. The result was that the entire premises were upheld. The working environment influences the capacity of an individual to work Secure, professional and organizational performance goals compatible. The working environment influences the capacity of an individual to work Secure, professional and organizational performance goals compatible. The employees need to be trained to handle job workload effectively and efficiently. The current study shows that improving working conditions leads to better enactment of employees. It could lead to improved organizational success due to employee retention and retention efforts to perform well in their workplaces. The present study reveals that improving working conditions leads to higher performance of employees. Improved organizational success due to work-life balance and retention efforts to perform well in their workplaces.